The Song of Disappearance: Memory, History, and Testimony in the Poetry of Antonio Gamoneda - Daniel Aguirre-Oteiza (Studies in 20th & 21st Century Literature, 2012)
This essay explores Antonio Gamoneda’s poetry as an Adornian form of testimony. With its enigmatic foregrounding of lies, the book-length poem Descripción de la mentira ‘Description of the Lie’ can be read as a “contradictory testimony” in which the act and memory of witnessing go, as it were, underground—only to resurface, rife with loss, years after Spain’s transition from dictatorship to democracy. Yet the abstruse character of this poetic writing prevents readers from drawing straightforward political truths about Spanish history from the poem. Losses are inscribed in the text catachrestically, as they truly are: losses. Gamoneda’s poetry has been read amid changing representations of Spain’s recent past, and thus contrastingly seen as an “undecipherable symbolic code” and as “realm of memory.” This reading, which draws on Holocaust studies, allows for a redefinition of the fraught place of modern poetry in the field of Hispanic cultural studies. Examining Descripción de la mentira within the context of the debate about historical memory in Spain sheds light on the theoretical difficulties that dominant aesthetic tendencies encounter in the study of how Spanish poets of recent decades try to establish a dialogue with the reader regarding society, memory, and reality.
Keywords: memory; poetry; Antonio Gamoneda; history; holocaust studies; modern poetry; Hispanic cultural studies; society; reality; dictatorship